2017
DOI: 10.26480/mjsa.01.2017.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Chenopodium quiona Wild under Naturally Salt Affected Soils

Abstract: Salinity and sodicity is today one of the most shocking threat in the irrigated agriculture. Mostly this is an abiotic strain that influences germination and plant growth. Quinoa (Chenopodium quinoa Wild.) has garnered much attention in recent years because it is an excellent source of plant-based protein and is highly tolerance of soil salinity and sodicity. Protein content in most quinoa accessions has been reported to range from 12 to 17%, depending on variety, environment, and input sit is traditionally ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Earlier, Lambertz et al [ 10 ] reported a higher carcass fat percentage in buffaloes following supplementation with a 2.0% body weight of concentrate, while Pimpa et al [ 37 ] failed to improve the warm and cold carcass yield of the cattle when fed with 5% fat. Nevertheless, the average carcass yield of the Murrah cross and the swamp buffaloes in this study was markedly lower than the pure-breed Murrah buffaloes, as reported by Biswas and Rajkumar [ 3 ] and Arshadullah et al [ 46 ], likely due to breed differences and the higher proportion of non-edible parts [ 16 , 47 ]. In fact, the Murrah cross in this study recorded a high carcass bone percentage ( p < 0.05).…”
Section: Discussionmentioning
confidence: 42%
“…Earlier, Lambertz et al [ 10 ] reported a higher carcass fat percentage in buffaloes following supplementation with a 2.0% body weight of concentrate, while Pimpa et al [ 37 ] failed to improve the warm and cold carcass yield of the cattle when fed with 5% fat. Nevertheless, the average carcass yield of the Murrah cross and the swamp buffaloes in this study was markedly lower than the pure-breed Murrah buffaloes, as reported by Biswas and Rajkumar [ 3 ] and Arshadullah et al [ 46 ], likely due to breed differences and the higher proportion of non-edible parts [ 16 , 47 ]. In fact, the Murrah cross in this study recorded a high carcass bone percentage ( p < 0.05).…”
Section: Discussionmentioning
confidence: 42%
“…Shen et al divided risks into internal, external and project-level risks by investigating the main risks in publicprojects and the management in the projects (Shen et al 2006, Yun et al 2018. Some researchers found that PPP project financing, especially capital market financing, plays an important role in the success of PPP projects (Regan et al 2011, Arshadullah et al 2017. In another study, scientists have constructed a PPP project performance index system with 5 kinds and 48 indexes by questionnaires (Yuan et al 2011.…”
Section: Introductionmentioning
confidence: 99%